Genotype by environment interaction and yield stability analysis of bread wheat (Triticum aestivum L.) varieties in East Gojjam Zone, Northwest Ethiopia - Alemnesh Eskezia; Habtamu Kefale; Mekonen Asrat (Heliyon, 2025)
Bread wheat (Triticum aestivum L.) is vital for over a third of the global population but faces significant production challenges due to limited adaptable varieties, poor management practices, and environmental factors. New wheat varieties often fail in unfamiliar environments, leading to crop loss. To address this issue, a study was conducted to evaluate the adaptability, performance, and yield stability of recently released high-performing wheat varieties over two years (2020/2021 and 2021/2022) in four districts of the East Gujjar Zone: Machakel, Debre Elias, Gozamin, and Baso-Liben. The trials were set up using a randomized complete block design (RCBD) with three replications, and data were collected on the main traits such as days to heading, maturity, plant height, tiller number, spike length, spikelet's per spike, biomass, and grain yield. AMMI and GEE biplot analysis were used to study genotype by environmental interaction. The combined analysis of variance for grain yield showed highly significant effects (P < 0.001) due to genotype (4.98 %), environment (66.83 %), and genotype × environment interaction (31.96 %). Grain yield varied across the environments, ranging from 3.72 t ha−1in Baso-Liben to 3.11 t ha−1 in Machakel. Among the genotypes, Ogolcho had the highest mean yield (4.55 t ha−1), whereas Wane had the lowest (2.70 t ha−1). Genotype-by-environment interaction biplot analysis grouped the eight test environments and six genotypes into two mega-environments and three genotype groups. Wane, Lemu, and Ogolcho were the stable genotypes. This analysis identified the most favorable districts for wheat production and highlighted Ogolcho as the most productive wheat variety in the study area. The results suggest that farmers in these districts should adopt Ogolcho to enhance wheat yield and increase their income.